Does Government Ideology Matter in Monetary Policy? – A Panel Data Analysis for OECD Countries - Ansgar Belke; Niklas Potrafke (Rheinisch-Westfälisches Institut für Wirtschaftsforschung (RWI), 2009)
This paper examines the effect of government ideology on monetary policy in a quarterly data set of 15 OECD countries in the period 1980.1-2005.4. Our Taylor-rule specification focuses on the interactions of a new time-variant indicator for central bank independence and government ideology. The results suggest that leftist governments did not decrease short term nominal interest rates at all. In contrast, short term nominal interest rates were higher under leftist governments. A potential reason for this finding might be that leftist governments have sought to make a market-oriented policy shift by delegating monetary policy to conservative central bankers.
Keywords: E52; E58; D72; C23; 330; Monetary policy; Taylor rule; government ideology; partisan politics; central bank independence; panel data; Geldpolitik; Taylor-Regel; Zentralbankautonomie; Ideologie; OECD-Staaten